Diagnosis And Management Of Pulmonary Tuberculosis In Hiv With Severe Immunodeficiency - Rizki, Fitri Amelia; Medison, Irvan; Anggrainy, Fenty (PROFESSIONAL HEALTH JOURNAL, 2025)
The total number of TB cases in Indonesia is 969,000. This figure represents a 17% increase compared to 2020. SITB 2022 data shows there are 15,375 cases of co-infection of pulmonary TB with HIV. The treatment success rate for pulmonary TB co-infection with HIV in Indonesia in 2022 is 71%. This is still far from the national target of 90%.This case report discusses a 33-year-old man with pulmonary TB and TB lymphadenitis with HIV at clinical stage 4. The CD4 count was 10 cells/mm3. The degree of immunodeficiency suffered by this patient is severe immunodeficiency. The management was to administer OAT first, followed by ART within 2 weeks after OAT was administered and well tolerated. OAT was administered for 9 months due to the presence of TB lymphadenitis. Treatment evaluation showed clinical improvement and the patient did not develop IRIS. The incidence of IRIS in patients with TB is 8%-43%. Factors influencing the occurrence of IRIS include the CD4 count at the start of ART.